2022
DOI: 10.1186/s12937-022-00801-0
|View full text |Cite
|
Sign up to set email alerts
|

“We think about the quantity more”: factors influencing emerging adults’ food outlet choice in a university food environment, a qualitative enquiry

Abstract: Background In recent decades, the food environment has seen rapid transformation globally, altering food availability and access along with how people interact with the food environment and make food-related choice. Objectives & method This explorative study aimed to identify the factors that shape the decision-making process for food outlet choices among emerging adults in a Ghanaian University food environment. The study uses focus group disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 67 publications
2
6
0
Order By: Relevance
“…Particularly, meal plans and university food outlets were the major themes mentioned by the participants in this category. This is consistent with findings from recent studies where university food and food environment characteristics were identified as important factors for enabling healthy and sustainable eating behaviours (Lee et al , 2019; Mensah and Oyebode, 2022). Marquis et al also concluded that action to increase food variety and convenient meals is required in the residence halls in university campuses (Marquis et al , 2019).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Particularly, meal plans and university food outlets were the major themes mentioned by the participants in this category. This is consistent with findings from recent studies where university food and food environment characteristics were identified as important factors for enabling healthy and sustainable eating behaviours (Lee et al , 2019; Mensah and Oyebode, 2022). Marquis et al also concluded that action to increase food variety and convenient meals is required in the residence halls in university campuses (Marquis et al , 2019).…”
Section: Discussionsupporting
confidence: 92%
“…Within the students' social environment, family, particularly parents, were the most important determinants of sustainable eating behaviours, followed by friends/peers, as students spend most of their time with their friends/peers when they are on campus. This has been highlighted in others studies, where it was found that parents impact diet trajectory patterns of young adults (Appannah et al, 2021), and friends have major influences on food choices due to time spent together and the need to be accepted by the social group (Malan et al, 2020;Mensah and Oyebode, 2022). Furthermore, eating was considered a social activity for many of the participants, which influenced their food choices based on their social group.…”
Section: Determinants Of Sustainable Eating Behavioursmentioning
confidence: 81%
See 1 more Smart Citation
“…This is consistent Fig. 4 Food outlet healthiness with qualitative findings from students in our study university [34] and a non-university context in China in a study that used the GIS method [46]. The study assessed the proximity/clustering of food-outlets around departmental buildings (including lecture rooms) and halls/hostels of residence, as these are the places students spend most of their time on campus.…”
Section: Discussionsupporting
confidence: 79%
“…That is, the prevailing characteristics of the University foodscape may be a materialised reflection of students' longstanding preferences. Qualitative research among UK and Bangladeshi students have suggested that academic demands on time (among students in this university [34]) and the lack of cooking skills among young university students make eating-out a convenient choice [58,59]. While all these reasons may not be the case among students at our study university due to differing cultural contexts, the findings here are consistent with the results from an urban poor non-student community in Ghana using the GIS method [5] and the Xi Hu district of China [46] showing a high number of outof-home cooked food and fast-food restaurants, respectively.…”
Section: Discussionmentioning
confidence: 99%